Immunogenetic protective factors in Genetic Generalized Epilepsy - Chaves, João (2021)
Background: Genetic Generalized Epilepsies (GGEs) are a heterogeneous group of syndromes characterized by generalized seizure activity that affects both hemispheres, with mainly genetic causes. Neuroinflammation has been established as an important mechanism in epileptogenesis. The ability to develop an appropriated immune response is strongly determined by immunogenetic factors. In this setting, our aim was to evaluate potential associations between GGEs and immunogenetic factors. Methods: The rs16944 (IL-1β -511 T > C) polymorphism and the HLA-DRB1 locus were genotyped in a Portuguese GGE population. Association with two clinicopathological features, photosensitivity and refractoriness, was investigated. This case-control study included 323 GGE patients (187 F, 136 M, 34.0 ± 13.9 years of age), 145 of which with JME diagnosis (88 F, 57 M, 34.1 ± 14.0 years), and 282 healthy controls (174 F, 108 M, 37.7 ± 11.6 years). Results: Decreased frequencies of the HLA-DRB1*09 and DRB1*13 alleles were observed in the GGE population. HLA-DRB1*07 frequency was increased in JME. Rs16944 allelic frequencies were similar between patients and controls. Conclusions: These results, not entirely consistent with previous reports, suggest that HLA molecules may have a complex role in epileptogenesis.